2023
DOI: 10.3390/cancers15092462
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Pulmonary Metastases from Melanoma in Oligometastatic Patients: Results from a Multicentric Study in the Era of Immunoncology and Targeted Therapy

Abstract: In the last decade, the emergence of effective systemic therapies (ESTs) in the form of both targeted and immuno-based therapies has revolutionized the treatment of patients with advanced stage III and stage IV melanoma. Even though lungs represent the most frequent site of melanoma metastases, only limited data are available on the role of surgery in isolated pulmonary metastases from malignant melanoma (PmMM) in the era of ESTs. The aim of this study is to describe the outcomes of patients who underwent meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…At the time of diagnosis, approximately 4% of patients with melanoma have distant metastasis [ 53 ]. Several variables, including tumor pathology, mutations (as summarized above), and biomarkers, have been shown to affect the ability of melanoma cells to metastasize, which, in turn, affects patient outcomes [ 54 ].…”
Section: The Role Of Metastectomy In Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of diagnosis, approximately 4% of patients with melanoma have distant metastasis [ 53 ]. Several variables, including tumor pathology, mutations (as summarized above), and biomarkers, have been shown to affect the ability of melanoma cells to metastasize, which, in turn, affects patient outcomes [ 54 ].…”
Section: The Role Of Metastectomy In Melanomamentioning
confidence: 99%
“…However, those studies that showed no benefit of metastasectomy are much less likely to be reported, which is a common occurrence with negative studies in general. However, some studies, even with positive (albeit modest) reports of benefits from metastasectomy, caution about the role of metastasectomy in metastatic melanoma because of this bias [ 53 , 78 , 79 , 80 ]. Overall, it is imperative to not only consider this bias for metastasectomy but also recognize that metastasectomy may provide benefits for highly select patients with metastatic disease, particularly for those in whom systemic therapies, often based on tumor mutational targets, may have minimized the tumor burden.…”
Section: The Role Of Metastectomy In Melanomamentioning
confidence: 99%